História dos trabalhadores de frigorífico em Francisco Beltrão-PR (1980-2020) - Tostes, Suzane Conceição Pantolfi (2022)
This thesis is the result of a study on slaughterhouse workers in Francisco Beltrão – PR between the years 1980 – 2020. From their life and work trajectories, we analyze a historical context marked by migration and the formation of industrial occupations in Francisco Beltrão in the last four decades. We identified work trajectories (before, during and after) of industrial occupations, meanings and meanings about the experiences lived and shared by people who occupied jobs in agribusinesses such as Sadia. In addition, it was possible to follow the social formation of a group of working – class neighborhoods known as “Cidade Norte”, located in the municipality of Francisco Beltrão – PR, something related to migrations, the search for employment, the formation of housing, sociability, exploitation of work and the acquisition of social rights. We make use of interviews, draft laws, journalistic sources, photographs, and specialized bibliography, located in the time and space of the research, to bring to light a social experience of common people that translates a historical period of changes and formation of the industrial proletariat in cities in the interior of Paraná.